Madrasah Tsanawiyah Teacher’s Formative Assessment Practices in EFL Classroom - Mubarokah, Rizqiyatul; Susilawati, Susilawati; Winarto, Eline Rozaliya (Universitas Subang, 2026)
This study aims to analyze the formative assessment practices implemented by English as a Foreign Language (EFL) teachers at the Madrasah Tsanawiyah level. This focus identifies the obstacles that prevent the teacher from conducting formative assessment optimally. This could relate to time constraints, large class sizes, and student diversity. The research employs a qualitative approach with a descriptive design, where data were collected through classroom observations and document analysis. The participants consisted of one EFL teacher. The findings reveal that the teacher applied four main formative assessment techniques: (1) questioning, (2) group discussions, (3) student presentations, and (4) assignments or homework. These techniques can help monitor students' learning progress and increase their participation, although their effectiveness varies depending on classroom dynamics and student characteristics. The study contributes to the broader understanding of formative assessment implementation in Islamic junior high school settings, an area that has received limited research attention compared to other educational levels. The findings of this study contribute concretely to the field in three specific ways. First, for EFL teachers at the MTs level, it provides a validated inventory of practical, low-preparation formative assessment strategies that can be immediately applied in large classrooms to enhance student speaking and writing skills. Second, for educational practitioners and curriculum developers, it identifies the specific types of feedback that most effectively boost student engagement, offering a blueprint for revising the English curriculum to include structured formative checkpoints. Third, for the Madrasah institution itself, the results highlight critical areas for professional development, enabling the school administration to organize targeted training workshops that address the real-world challenges teachers face in implementing classroom-based assessments.